The impact of salt on blood pressure and cardiovascular target organ damage - Mashao, Mapula Mercy (My University, 2020)
Cardiovascular events such as hypertension, renal failure and arterial stiffness are attributed to dietary sodium intake as measured using urinary sodium excretion. In this thesis, I investigated the relationship between urinary sodium excretion and blood pressure and the relationship between urinary sodium excetion and arterial stiffness in a unique salt sensitive cohort of black South Africans. Previous studies conducted to investigate the relationship between sodium and blood pressure in our cohort of African participants have yielded contradictory results. With the high prevalence of obesity in this population, it is possible that these contradictory findings are due to the masking effects of obesity on this relationship. Ambulatory blood pressure was determined using a Spacelabs 90207 (Spacelabs Inc., Redmond, Washington, USA) monitor. In a sample of 547 individuals, I demonstrated that there is no independent relationship between 24-hour Na+ excretion and blood pressure in the total population sample, however when participants were stratified according to body mass index (BMI) status, there was a significant association between 24-hour Na+ excretion and ambulatory blood pressure in the normal-BMI participants but not in the overweight/obese participants. I concluded that 24-hour urinary Na+ excretion, was associated with increased ambulatory blood pressure but this relationship was masked because of a high proportion of overweight/obese individuals in this population. Because I demonstrated a masking effect of obesity on the relationship between urinary sodium excetion and blood pressure in the previous chapter, I decided to investigate a possible masking effect of obesity on the relationship between urinary sodium excretion and arterial stiffness as measured using carotid-femoral pulse wave velocity. Increased arterial stiffness as measured by carotid femoral pulse wave velocity is an independent predictor of cardiovascular morbidity and mortality. In the present study, I measured arterial stiffness using carotid femoral pulse wave velocity. This was done using a high-fidelity SPC-301 micromanometer (Millar Instrument, Inc., Houston, Texas) interfaced with a SphygmoCor software (AtCor Medical Pty. Ltd., West Ryde, New South Wales, Australia); version 9.0. In the present study, I demonstrate in 547 participants of African ancestry that obese individuals have higher pulse wave velocity when compared with normal weight individuals (7.0±3.0 vs 5.9±2.3). Urinary sodiumexcretion was significantly lower in overweight/Obese female participants compared to normal weight individuals (99.5±68.6 vs 121.5±99.4). Leptin levels were also higher in the overweight/obese group when compared with the normal weight group irrespective of gender. More importantly, I show that 24-hour urinary sodium excretion is an independent predictor of arterial stiffness as measured by carotid femoral pulse wave velocity in normal weight females (p = 0.0002) but not in overweight/obese females. This relationship was however absent in males irrespective of BMI status. Therefore, the study suggests that obesity masks the relationship between urinary sodium excretion and pulse wave velocity in females in a cohort of black South Africans. Due to a high prevalence of obesity in the Black South African population and because I have reported the masking effects of obesity on the relationship between urinary sodium excretion and blood pressure and the relationship between urinary sodium excretion and arterial stifness in the previous chapters, I decided to investigate the relationship between urinary sodium excretion and blood pressure in a cohort of normal weight black South Africans. I measured conventional blood pressure and collected 24-hour urinary Na+ excretion in all participants. Anthropometric measurements were taken, and standard questionnaire was used to collect data on family medical history, use of medication and dietary information. Of the 750 participants with complete measurements, 236 participants had normal BMI and were included in the statistical analyses. The mean 24-hour urinary Na+ excretion was 114 mmol/day. Multivariate regression analyses showed a significant inverse relationship between systolic BP and 24-hour urinary Na+ excretion (r = -0.16; p=0.0082) and between diastolic BP and 24-hour urinary Na+ excretion (r = -0.14; p=0.02). The findings from this study reveal a negative relationship between 24-hour urinary sodium excretion and blood pressure, which is in complete contrast to previously established relationships. This might point to a unique renal sodium handling in this cohort. The results have far reaching implications, as they suggest that urinary sodium excretion cannot be used to estimate dietary sodium intake in this population as there might be some sodium retention going on despite increases in blood pressure. I believe that future research is needed to determine the mechanisms that govern the relationship between urinary sodium excretion and blood pressure in this population and that other methods should be used to estimate dietary sodium intake in this population. In conclusion, the data presented in this thesis have identified a possible role of obesity in interfering with the relationship between urinary sodium excretion and blood pressure. I have also identified a possible role of obesity in interfering with the relationship between urinary sodium excretion and a cardiovascular target organ damage like arterial stiffness. The data in this thesis also identified an inverse relationship between urinary sodium excretion and blood pressure in normal weight individuals of African ancestry. All these have added new and unique knowledge concerning obesity and cardiovascular disease.
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy to the Faculty of Health Sciences, School of Physiology, University of the Witwatersrand, Johannesburg, 2020